Brain Drain and Its Effects on Livelihood: An Analysis of Phalewas Municipality, Nepal - Panta, Saroj Raj (Dhaulagiri Journal of Contemporary Issues, 2025)
This article explores the impacts of brain drain in Phalebas Municipality-7, Limithana, Parbat, Nepal. Brain drain is the global exchange of human resources and primarily involves the migration of skilled and educated individuals leaving countries. The main objective of this research is to investigate the causes of brain drain and its effects on their family in Phalebas Municipality-7, Limithana of Parbat District. This study is based on qualitative research methods, including descriptive and analytical research design. Data were collected using purposive sampling of 28 households. This study has applied observation and interview tools of data collection. The findings of this study show that brain drain has more negative than positive effects on households. Due to a lack of job opportunities, political instability, infrastructure problems, monkey terrorism, low productivity, inadequate working environments, lack of skilled training, and imitation. Informants tend to be attracted to work abroad when they find better job prospects, and once they realize their skills have improved, they are more likely to stay overseas. This study concluded that brain drain has effects on livelihood in this study area. To address the negative effects due to brain drain for better livelihoods, focus on educating citizens, creating attractive career opportunities, and mobilizing knowledge and skills. This research will be useful for academics, future researchers, and policymakers.